PERBANDINGAN PENGETAHUAN KESEHATAN REPRODUKSI ANTARA REMAJA LAKI-LAKI DAN PEREMPUAN DI JAKARTA - Pristya, Terry Y.R.; karima, Ulya Q; Herbawani, Chahya K (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
In Indonesia, the main problem of adolescent reproductive health is the lack of reproductive health information. It occurred due to poor of their knowledge. This study aimed to compare reproductive health knowledge between female and male adolescents. This cross-sectional study was conducted by online-based survey in Jakarta, Indonesia. The 438 samples of this study consisted of 244 female and 194 male adolescents. Data was collected with Google Forms. Logistic regression was used to analyze the data of this study. A proportion of male adolescents have more poor knowledge (21.1%) than female adolescents (13.9%). The odds of male adolescents were 1.66 times more likely (95% CI 1.00-2.73) to have poor reproductive health knowledge than female adolescents. In separate analyzes between females and males, the role of education institutions has a significant relationship with reproductive health knowledge in females (P-value = 0.039). However, in male adolescents, it was not. Health promotion from educational institutions is needed to increase adolescent reproductive health knowledge, especially for male adolescents.